Strategi Pengembangan Usaha Perbenihan Padi Bersertifikat di Subak Guama, Kecamatan Marga, Kabupaten Tabanan - Ni Made Ayu Citra Laksmi; Wayan Windia; Ketut Suamba (Universitas Udayana, 2017)
ABSTRACTBusiness Development Strategy Certified Rice Seed On Subak Guama,Marga District, Tabanan RegencyThe increasing rate of population growth led to increased demand for food. Inorder to achieve food security, the use of certified seeds is one of the factors thatinfluence the improvement of yield and quality of production. Attempt to capturethese opportunities, Subak Guama need to make strategic business development ofcertified rice seed. The purpose of research is to investigate alternative strategiesand priorities appropriate strategies run by Subak Guama in the development ofcertified rice seed business.The research location was at Subak Guama. Respondents were selectedpurposively regarding their expertise and knowledge of the research. Primarydata were collected focus group discussions, surveys, and in-depth interviews.Secondary data were collected from publications. Formulation of alternativestrategies and priority strategies using SWOT matrix analysis and analysisQSPM.The results show alternative strategies of business development certifiedrice seed include: 1) expand market share in order to meet the potential needs ofseeds, 2) the formation of youth groups farmer, 3) improving the quality of humanresources, 4) empowerment of farmers through the capital strengthening farming5) integrated pest and disease control, and 6) optimization of the certified riceseed business. The result also shows that the priority strategy selected is capitalstrengthening farming.In supporting the development of business certified rice seed, members of SubakGuama is expected to strengthen the capital to apply for credit farming throughfinancial institutions/banks so as to increase production and develop productsseed varieties vary, increase access to a wider market so as to maintain its marketposition has been achieved, as well as more effective cooperation betweenfarmers with KUAT Subak Guama.Keywords: SWOT, QSPM, Rice Seed, Subak